Antagonistic Activity of Lactobacillus reuteri Strains on the Adhesion Characteristics of Selected Pathogens - Singh, Tejinder P.; Kaur, Gurpreet; Kapila, Suman; Malik, Ravinder K. (Frontiers in Microbiology, 2017)
Adhesion ability of probiotics is the key factor that decides their colonization in the gastrointestinal tract and potential to inhibit pathogens. Therefore, adhesion ability can be considered as a key determinant for probiotic efficacy. Presents study documents the antagonistic activity of viable/untreated, Lithium chloride (LiCl) treated or heat-killed forms of eight probiotic Lactobacillus reuteri strains on the adhesion characteristics of selected pathogens. All strains investigated were able to adhere to Caco-2 cells. L. reuteri strains tested were able to inhibit and displace (P < 0.05) the adhesion of Escherichia coli ATCC25922, Salmonella typhi NCDC113, Listeria monocytogenes ATCC53135 and Enterococcus faecalis NCDC115. The probiotic strain L. reuteri LR6 showed the strongest adhesion and pathogen inhibition ability among the eight L. reuteri strains tested. In addition, the abilities to inhibit and to displace adhered pathogens depended on both the probiotic and the pathogen strains tested suggesting the involvement of various mechanisms. The adhesion and antagonistic potential of the probiotic strains were significantly decreased upon exposure to 5M LiCl, showing that surface molecules, proteinaceous in nature, are involved. The heat-killed forms of the probiotic L. reuteri strains also inhibited the attachment of selected pathogens to Caco-2 cells. In conclusion, in vitro assays showed that L. reuteri strains, as viable or heat-killed forms, are adherent to Caco-2 cells and are highly antagonistic to pathogens tested in which surface associated proteins play an important role.